Urban Air Pollution and Testosterone Plasma Level of Traffic Policemen in Jakarta - Ramdhan, Doni Hikmat; Modjo, Robiana; Rachmawati, Sutrani; Kurniasari, Fitri (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
This study aims to investigate the concentration of traffic air pollution and the level of testosterone, fasting glucose, cortisol, and lipid profile among traffic police in Jakarta. Testosterone plasma and blood biochemicals in traffic police and the police officer were analyzed using ELISA kit. Air quality data from the Regional Environmental Agency (BPLHD) Jakarta 2012 were used for the characterization of exposure. The analysis used a t-test and linear regression test to show the relationship levels of pollutants exposure with the effects of reproductive dysfunction (p<0.05). The average plasma levels of testosterone in the traffic police 543.6 ± 170.5 mg/dL, which is higher than the police at the office 456.2 ± 133.2 mg/dL. The average plasma cholesterol levels of police at the office is 212.3 ± 42.0 mg/dL, which is higher than the traffic police 200.0 ± 40.2 mg/dL. On average fasting glucose levels police at the office is 90.0 ± 13.1 mg/dL, while traffic police 84.2 ± 5.9 mg/dL. The testosterone levels of traffic police are higher than the official police, and traffic police exposed to pollutants have lower fasting glucose levels than police officers in offices. Keywords: PM, plasma testosterone, reproductive function.